Are we prepared to lose our precious land? Community approaches to pasture and cropland restoration in Marigat District, Kenya - Lenachuru, Clement Isaiah, speaker (Colorado State University. Libraries, 2012)
Global concerns about deforestation caused by fuelwood shortages, prompted introduction of in Lake Baringo area early 1980's. is on IUCN's new list of 100 world's worst invasive alien species. has survived where other tree species have failed and in many cases become a major nuisance. In Baringo, is reported to depress the growth and survival of indigenous vegetation around it, and farmers claim to have lost their farmlands, reduce grazing potential and space of pasture lands. Its invasion in Baringo area in the last 10-15 years has attracted national attention and contradictory responses from responsible agencies. Unlike in other parts of the world where it has been introduced, potential benefits have not been realized. Strong local calls for eradication and replacement appears to be well justified. problem is further compounded by the fact that the land is communally owned. Thus, where land is held under common property arrangements, management responses to the invasive species require cooperation among affected individuals. This project plans to actively engage on regular basis and mobilize the local community to work cooperatively in checking the spread of this shrub, at the same time seek alternative land uses that will help to control any further invasions.
Presented at the Spring 2012 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Innovations in Communities Around the World", April 3, 2012, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Clement Isaiah Lenachuru is a PhD candidate in the Department of Forest and Rangeland Stewardship, CSU. Clement obtained a Diploma (Range Management), Bachelors (Natural Resources Management (Wildlife major) and Master's Degree (Natural Resources-Human Ecology) from Egerton University. He joined CSU from Egerton University, Njoro, Kenya, where he served as an Assistant Lecturer in the Faculty of Environment and Resources Development, Department of Natural Resources. He also served on the committee that deals with research needs in Kenya's drylands. He has been awarded a Ford Foundation International Fellowship. His current research interests are in climate change and indigenous knowledge systems of the pastoralists in Kenya. He has published with colleagues in the area of "Role of Formal Education in Assets Diversification among the Ilchamus in Baringo District Kenya". He has also presented a number of unpublished workshop papers in the area of environmental management and effects of invasive weeds (the case ) in pastoral lands in Kenya. Clement has also served for 4 years (2005-2009) as national coordinators for a non-governmental organization that voices and advocates for the pastoralist friendly policies in Kenya.
Accessibility features: Unedited transcript.
To request an edited transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: population growth; pastoral production systems; demand for resources; deforestation; eradication